Respostas

2014-05-23T00:57:32-03:00
1) x² -7x +6=0
a=1  b=-7  c=6
Δ= b² -4.a.c
Δ=(-7)² -4 . 1 . 6
Δ= 49 - 24
Δ= 25
x=  \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(-7)+- \sqrt{25} }{2.1}
x'= \frac{7+5}{2}
x'= \frac{12}{2}
x'= 6
x''= \frac{7-5}{2}
x''= \frac{2}{2}
x''= 1


2) 2x² -8x +8=0
a= 2  b= -8  c=8
Δ= b² -4.a.c
Δ=(-8)² -4 . 2 . 8
Δ=64 - 64
Δ=0
x=  \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(2)+- \sqrt{0} }{2.2}
x'= \frac{-2+0}{4}
x'= \frac{-2}{4}
x'= -0,5
x''= \frac{-2-0}{4}
x''= \frac{-2}{4}
x''= -0,5


3) x² +5x -6=0
a= 1  b=5  c= -6
Δ= b² -4.a.c
Δ=(5)² -4 . 1 . -6
Δ= 25 + 24
Δ= 49
x=  \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(5)+- \sqrt{49} }{2.1}
x'= \frac{-5+7}{2}
x'= \frac{2}{2}
x'= 1
x''= \frac{-5-7}{2}
x''= \frac{-12}{2}
x''= -6


4) 3x² +2x -5=0
a= 3  b= 2  c= -5
Δ= b² -4.a.c
Δ=(2)² -4 . 3 . -5
Δ= 4 + 60
Δ= 64
x=  \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(2)+- \sqrt{64} }{2.3}
x'= \frac{-2+8}{6}
x'= \frac{6}{6}
x'=1
x''= \frac{-2-8}{6}
x''= \frac{-10}{6}
x''= 1,666...


5) x² -10x +24=0
a= 1  b= -10  c= 24
Δ= b² -4.a.c
Δ=(-10)² -4 . 1 . 24
Δ= 100 - 96
Δ= 4
x=  \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(-10)+- \sqrt{4} }{2.1}
x'= \frac{10+2}{2}
x'= \frac{12}{2}
x'= 6
x''= \frac{10-2}{2}
x''= \frac{8}{2}
x''= 4


1 5 1